The Mental Handsomeness Among University Students - Hussein Kareem Mohammed Al-enzi (Academia Open, 2026)
General Background: Mental attractiveness, or mindfulness, represents a cognitive strategy enabling individuals to engage flexibly with new experiences and generate creative solutions, playing a crucial role in academic performance and psychological well-being. Specific Background: University students, as key contributors to societal development, require enhanced mental capabilities to navigate complex learning environments and manage psychological stress effectively. Knowledge Gap: Despite its importance, no prior research has examined mental attractiveness among Arab or Iraqi university students, leaving a significant void in understanding how this cognitive trait manifests across different demographics in higher education settings. Aims: This study investigated the degree of mental attractiveness among Wasit University students and examined statistically significant differences based on gender (male-female) and academic specialization (scientific-humanities). Results: Analysis of 400 students using Langer's (1992) mental attractiveness scale revealed that university students possess high levels of mental attractiveness (M=49.70, SD=4.65), with no statistically significant differences according to gender (F=0.852) or specialization (F=0.026). Novelty: This represents the first empirical investigation of mental attractiveness among university students in the Iraqi context, establishing baseline measurements for this population. Implications: The findings suggest that mental attractiveness transcends gender and disciplinary boundaries, indicating universal cognitive flexibility among university students that can inform educational interventions promoting mindful learning practices and psychological resilience across diverse academic programsKeywords : Mental Attractiveness, University Students, Langer Theory, Gender Differences, Academic SpecializationHighlight : University students demonstrate high levels of mental attractiveness regardless of background. Gender and academic specialization show no significant impact on mental attractiveness. Mental attractiveness enhances psychological well-being, self-confidence, and academic performance